Treatment of Chronic Atrial Fibrillation During Surgery for Rheumatic Mitral Valve Disease - Gonçalves,Flavio Donizete (2016)
Abstract Introduction: The result of surgical ablation of atrial fibrillation remains controversial, although prospective and randomized studies have shown significant differences in the return to sinus rhythm in patients treated with ablation versus control group. Surgery of the Labyrinth, proposed by Cox and colleagues, is complex and increases the morbidity rate. Therefore, studies are needed to confirm the impact on clinical outcomes and quality of life of these patients. Objective: To analyze the results obtained in the treatment of atrial fibrillation by surgical approach, by Gomes procedure, for mitral valve surgery in patients with rheumatic heart disease associated with chronic atrial fibrillation. Methods: We studied 20 patients with mitral valve dysfunction of rheumatic etiology, evolving with chronic atrial fibrillation, submitted to surgical treatment of valvular dysfunction and atrial fibrillation by Gomes procedure. Results: The mean duration of infusion ranged from 65.8±11.22 and aortic clamping of 40.8±7.87 minutes. Of 20 patients operated, 19 (95%) patients were discharged with normal atrial heart rhythm. One (5%) patient required permanent endocardial pacing. In the postoperative follow-up of six months, 18 (90%) patients continued with regular atrial rhythm, one (5%) patient returned to atrial fibrillation and one (5%) patient continued to require endocardial pacemaker to maintain regular rhythm. Conclusion: Gomes procedure associated with surgical correction of mitral dysfunction simplified the surgical ablation of atrial fibrillation in patients with rheumatic mitral valve disease and persistent atrial fibrillation. The results showed that it is a safe and effective procedure.